Cutting edge concepts: Does bilirubin enhance exercise performance? - Flack, Kyle D.; Vítek, Libor; Fry, Christopher S.; Stec, David E.; Hinds, Terry D. (Frontiers in Sports and Active Living, 2023)
Exercise performance is dependent on many factors, such as muscular strength and endurance, cardiovascular capacity, liver health, and metabolic flexibility. Recent studies show that plasma levels of bilirubin, which has classically been viewed as a liver dysfunction biomarker, are elevated by exercise training and that elite athletes may have significantly higher levels. Other studies have shown higher plasma bilirubin levels in athletes and active individuals compared to general, sedentary populations. The reason for these adaptions is unclear, but it could be related to bilirubin's antioxidant properties in response to a large number of reactive oxygen species (ROS) that originates from mitochondria during exercise. However, the mechanisms of these are unknown. Current research has re-defined bilirubin as a metabolic hormone that interacts with nuclear receptors to drive gene transcription, which reduces body weight. Bilirubin has been shown to reduce adiposity and improve the cardiovascular system, which might be related to the adaption of bilirubin increasing during exercise. No studies have directly tested if elevating bilirubin levels can influence athletic performance. However, based on the mechanisms proposed in the present review, this seems plausible and an area to consider for future studies. Here, we discuss the importance of bilirubin and exercise and how the combination might improve metabolic health outcomes and possibly athletic performance.